2022
DOI: 10.1002/jcla.24235
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expressions of circulating lncRNA NEAT1 and microRNA‐125a are linked with Th2 cells and symptom severity in pediatric allergic rhinitis

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…In AR, aberrantly expressed circulating lnc-NEAT1 and miR-125a were associated with Th2 cell percentage and symptoms in pediatric AR. 148 In AD, Liew et al found decreased expression of miR-335 in AD lesions compared with healthy control skin. 149 Nuclear factor kappa-B (NF-κB) (p65) is a critical modulator of inflammatory immune response, and miR-124 is associated with inflammatory response and may constitute a new effector and regulator of NF-κB.…”
Section: Mechanismmentioning
confidence: 99%
“…In AR, aberrantly expressed circulating lnc-NEAT1 and miR-125a were associated with Th2 cell percentage and symptoms in pediatric AR. 148 In AD, Liew et al found decreased expression of miR-335 in AD lesions compared with healthy control skin. 149 Nuclear factor kappa-B (NF-κB) (p65) is a critical modulator of inflammatory immune response, and miR-124 is associated with inflammatory response and may constitute a new effector and regulator of NF-κB.…”
Section: Mechanismmentioning
confidence: 99%
“…Thirdly, a deeper understanding of ncRNAs holds promise for the development of diagnostic tools and treatments for AR is needed. Several other lncRNAs, including lncRNA HCP5, 45 LncRNA MIAT, 46 lncRNA NEAT1, 47 MALAT1, 48 lnc-THRIL, 49 Linc00632, 50 HOTAIRM1, 51 have been implicated in the pathogenesis of AR. Further research is required to confirm whether these lncRNAs interconnect and form a regulatory network that precisely controls the onset and severity of AR.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, histopathological specimens revealed that lncRNA-NEAT1 expression was significantly upregulated in the nasal mucosa of AR patients and positively correlated with disease symptom scores and inflammatory cytokine levels, suggesting that it could be used as a biomarker to assess the severity of AR disease [140]. Moreover, a recent study found that circulating-derived lncRNAs also 7 Mediators of Inflammation play an essential role in the pathogenesis of AR [147][148][149]. Wang et al [148] found that the exosome-derived lncRNA NEAT1 regulates the microRNA-511/NR4A2 signaling axis and then participates in the disease development of AR.…”
Section: Lncrna and Armentioning
confidence: 99%